Mystery and artistic veil – Widma [Phantoms] by Stanisław Moniuszko and Paweł Passini - Lisiecka, Katarzyna (Interdisciplinary Studies in Musicology, 2023)
The purpose of this paper is to analyse Moniuszko’s Phantoms with a particular focus on the relationships between music and libretto in order to compare them later with modern strategies of performances staged recently in Polish operas and concert halls. The source-historical context referring to cultural and perceptive aspects of Phantoms serves as a starting point. The question is also raised concerning the relationship and fusion of arts constituting that intriguing work. A search for dramaturgic-theatrical aspects of Moniuszko’s work assumes an attempt to capture a so-called ‘intentio operis’, created at the intersection of Mickiewicz’s text and musical intentions of the composer. The analysis was centered on selected aspects of dramaturgy of a few performances of ‘Phantoms’ staged at the Wratislavia Cantans Festival (2017, dir. P. Passini), the Wrocław Opera, (prem. 2018, dir. J. Fret), and the Polish Royal Opera (prem. 2017, dir. R. Peryt). All stagings were an interesting attempt to reinterpret a starting form of cantata bringing it closer to theatrical work. This paper intends to answer the following questions: what dramaturgic and theatrical strategies are generated by Moniuszko’s cantata? To what extent does the cantata nature of this music-textual work contributes to new theatrical interpretations? To what extent are modern stage productions the answer to an artistic potential present in its music-textual layer? Do the new projects of its visualization and dramatisation result, even indirectly, from the structural and staging potential of the work, or whether they attempt to add new artistic ideas in order to make Phantoms more attractive as a starting, incomplete, music-textual structure?